Paleomagnetic Biases Inferred From Numerical Dynamos and the Search for Geodynamo Evolution - Driscoll, Peter E.; Wilson, Cian (Frontiers in Earth Science, 2018)
The paleomagnetic record is central to our understanding of the history of the Earth. The orientation and intensity of magnetic minerals preserved in ancient rocks indicate the geodynamo has been alive since at least the Archean and possibly the Hadean. A paleomagnetic signature of the initial solidification of the inner core, arguably the singular most important event in core history, however, has remained elusive. In pursuit of this signature we investigate the assumption that the field is a geocentric axial dipole (GAD) over long time scales. We study a suite of numerical dynamo simulations from a paleomagnetic perspective to explore how long the field should be time-averaged to obtain stable paleomagnetic pole directions and intensities. We find that running averages over 20 − 40 kyr are needed to obtain stable paleomagnetic poles with α95<10°, and over 40 − 120 kyr for α95<5°, depending on the variability of the field. We find that models with higher heat flux and more frequent polarity reversals require longer time averages, and that obtaining stable intensities requires longer time averaging than obtaining stable directions. Running averages of local field intensity and inclination produce reliable estimates of the underlying dipole moment when reversal frequency is low. However, when heat flux and reversal frequency are increased we find that local observations tend to underestimate virtual dipole moment (VDM) by up to 50% and overestimate virtual axial dipole moment (VADM) by up to 150%. A latitudinal dependence is found where VDM underestimates the true dipole moment more at low latitudes, while VADM overestimates the true axial dipole moment more at high latitudes. The cause for these observed intensity biases appears to be a contamination of the time averaged field by non-GAD terms, which grows with reversal frequency. We derive a scaling law connecting reversal frequency and site paleolatitude to paleointensity bias (ratio of observed to the true value). Finally we apply this adjustment to the PINT paleointensity record. These biases produce little change to the overall trend of a relatively flat but scattered intensity over the last 3.5 Ga. A more careful intensity adjustment applied during periods when the reversal frequency is known could reveal previously obscured features in the paleointensity record.